Evaluasi Mengulum Es Batu dan Fruit Frozen terhadap Rasa Haus pada Pasien Congestive Heart Failure yang Menjalani Retriksi Cairan - Satti, Yunita Carolina; Irwandy, Fransisco (Jurnal Keperawatan Florence Nightingale, 2024)
Fluid restriction in Congestive Heart Failure patients often causes intense thirst. Thirst resulting from a fluid restriction program in CHF patients can be overcome by stimulating saliva to keep the oral mucosa moist and reduce complaints of thirst. To reduce the thirst of CHF patients, one way that can be done is to suck ice cubes and frozen fruit. This study aims to compare the differences in thirst in CHF patients who suck ice cubes and suck frozen fruit. This research is quantitative research with a quasi-experimental approach with a pre and post-test design with control group. The research location will be carried out at Labuang Baji Regional Hospital, Makassar. Participants were selected using Consecutive Sampling techniques. The instrument that will be used is Visual Analog scale. The results of analysis using the Mann-Whitney test showed that the mean rank value for chewing ice cubes was 8.4 and for the frozen fruit group it was 22.7. There was a significant difference between the decrease in the intensity of thirst in the group sucking ice cubes and frozen fruit. Where the difference in average decrease in thirst in the ice cube group was greater than in the frozen fruit suckling group. The results of the Mann Whitney test also showed 0.000 (p < 0.05), it can be concluded that there is a difference in the effectiveness of sucking ice cubes and frozen fruit on thirst in Congestive Heart Failure patients undergoing a fluid restriction program at Stella Maris Hospital, Makassar